Poligami di Indonesia: Analisis Praktik Hukum Keluarga Islam - Iswandi, Andi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This study aims to analyze the Islamic family law practices related to polygamy in the social, cultural, and legal context of Indonesia. The research method used is literature analysis and case studies to understand the implementation of polygamous practices and their impact on individuals, families, and society. The results show that polygamy in Islamic family law has complex implications. Although allowed in Islam, polygamy often causes controversy and conflict in contemporary society. The negative impacts of polygamous practices include injustice towards women and children, tension in family relationships, and complexity in inheritance arrangements and parental responsibilities. However, some views see polygamy as a solution to specific social problems, such as gender balance and protection for women without partners, as indicated by BPS data showing fewer men compared to women aged 60 and above, suggesting that men who wish to practice polygamy should marry older women. The analysis of Islamic family law practices related to polygamy emphasizes the need for a balance between understanding religious teachings, universal humanitarian values, and local socio-cultural contexts. This research underscores the importance of regulating polygamous practices within a fair legal framework that protects the rights of all parties involved to minimize negative impacts and maximize the social benefits of such practices.